Black Cumin Seeds Extract Increase Lymphocyte Activity in IFN-γ Secretion in Sprague Dawley Rat (SD) Induced by Dimethylbenzantracene - Akrom, Akrom; Hidayati, Titiek; Sagiran, Sagiran; Indrayanti, Indrayanti (Indonesian Society for Cancer Chemoprevention, 2019)
Interferon-gamma (IFN-γ) is one of the central cytokines in the anti-carcinogenesis immune response. Black cumin seeds (BCS) have an active content of thymoquinone and unsaturated fatty acids with biological activity as immunomodulators. This study aimed to determine the effect of administration of BCS extract on IFN-γ secretion activity by DMBA-induced SD rat lymphocytes. In vivo experimental study on DMBA-induced SD rats, BCS extract was given with three doses for two weeks before being induced and five weeks during DMBA induction. IFN-γ levels in lymphocyte culture supernatants were determined by the ELISA method. The difference in IFN-γ levels between groups was analyzed by ANOVA test, the significance of 95%. The results showed that administration of BCS extract for 14 days did not affect cellular composition toward the edge of the test animal. BCS extract can increase IFN-γ secretion activity by DMBA-induced SD rat lymphocytes.Keywords: black cumin seed, IFN-γ; DMBA: immunomodulator, carcinogenesis.